Analisis Perubahan Psikososial: Depresi dan Ansietas Selama Pandemi COVID-19 pada Kalangan Pelajar: Depresi dan Ansietas Selama Pandemi COVID-19 pada Kalangan Pelajar - Muhammad Mikail Athif Zhafir Asyura; Muhammad Farid Ar-Rizq; Rejoel Mangasa Siagian (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2021)
Background: The respiratory disease named novel coronavirus disease 2019 (COVID-19) was caused by the Severe acute respiratory syndrome-Coronavirus-2 (SARS-CoV-2) originated initially in Wuhan, China. Furthermore, the exponential spread of the virus forced many officials to employ strict lockdown and physical distancing measures to halt the transmission. Despite this, mass isolation only surfaces a plethora of problems, especially the increased prevalence in depression and generalized anxiety disorder (GAD). Both mental illnesses have been shown to increase during the pandemic due to a myriad of risk factors. Thus, in this study we aim to shed light on those risk factors, via a systematic review to determine which are the pivotal reasons for the increasing prevalence Methods: The review is done in accordance to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) guideline from a few online databases including: PubMed, Cochrane, Sciencedirect, Wiley Online Library, dan EBSCOhost Discussion: After analyzing 401 articles, 5 articles were chosen based on the inclusion criteria. The articles unanimously agreed on a few factors, namely: student status, gender, preexisting health conditions, and also emotional management as main risk factors of depression and GAD Conclusion: In conclusion, those risk factors should be put into consideration by policy makers in crafting protective measures against COVID-19 and other pandemics in the future in order to minimize its impact on the mental health of students and the overall community.